Implementation of the Application of Information and Communication Technology in Economics Learning (Case Study of SMA Negeri 1 Gowa) - Mustari, Mustari (Cita konsultindo, 2023)
The purpose of this article is to take a deeper look at the application of Information and Communication Technology (ICT) as a medium to assist learning in essential and optional schools. This article uses a writing survey strategy, more specifically by looking at several public and global diaries which will then be detailed using a content inspection procedure. The consequences of this research are: 1) in implementing ICT as a medium to help realize that there are various kinds of ICT-based media that can be used in learning exercises, but instructors must also be more careful in choosing ICT-based learning media that are used to enhance learning exercises, 2) The absence of ICT provision for educators is one of the fundamental obstacles that can make it difficult for educators to implement ICT in learning, and 3) instructor efforts in creating skills in the field in ICT, support and cooperation from various groups can encourage the implementation of ICT as a supporting medium the realization of learning activities can run more optimally and the nature of the teacher can also improve.